Innovation Management in Organizations: A Review on Responsible Innovation Practices - ALZAROONI, ABDALLA MAHMOUD (2023)
The study's purpose is to investigate the role of innovation management assessment, responsible innovation, policy perspective, and perception of responsible innovation in the successful implementation of responsible innovation processes. The data was collected through an online questionnaire, and the findings provide theoretical and practical insights. Mainly, researcher used the regression analysis to evaluate the collected data. The results support existing theories such as the "Triple Helix model," "Innovation System theory," "Diffusion of Innovation theory," and the "Knowledge Attitude Behavior" model, while also challenging some theories regarding the impact of policy perspectives on innovation success. The study highlights the significance of cultivating a positive outlook towards responsible innovation, establishing robust innovation management protocols, shaping supportive policies, and enhancing awareness and understanding of responsible innovation. The findings hold relevance for managers, policymakers, and stakeholders, emphasizing the importance of integrating ethical considerations, implementing responsible innovation strategies, and fostering collaboration. The study concludes with recommendations for organizations and policymakers in the UAE to effectively implement responsible innovation and build a sustainable innovation ecosystem.